Variations in characteristics and transport pathways of PM2.5 during heavy pollution episodes in 2013–2019 in Jinan, a central city in the north China Plain. (1st September 2021) - Wang, Gang; Zhu, Zhongyi; Zhao, Na; Wei, Peng; Li, Guohao; Zhang, Hanyu
Abstract: The characteristics and transport pathways of air masses vary during heavy pollution episodes (HPEs). Three categories of HPEs have been defined: HPE Ι, II, and III, corresponding to HPE durations of 1, 2, and at least 3 days, respectively. Sixty HPEs were investigated in this study. The number of HPEs decreased from 2013 to 2017 and then increased from 2017 to 2019, dominated by emission reductions and meteorological conditions. The average and maximum PM2.5 (i.e., aerodynamic diameter of <2.5 μm) concentrations during those HPEs in 2019 decreased by 5.6%–11.8% and 11.9%–38.5%, respectively, compared with those in 2013. The longer the duration of an HPE, the higher the PM2.5 concentration. Secondary inorganic aerosol concentrations and their contents in PM2.5 during HPE Ⅲ were found to be higher than those during HPEs Ι and Ⅱ, as secondary transformations of precursor gases are more intense during long-term HPEs. The dominant trajectories of airflow arriving in Jinan originated from the southern and southeastern regions during HPEs, realized using the Hybrid Single Particle Lagrangian Integrated Trajectory. The trajectories from the north and west of Jinan contained the highest PM2.5 concentrations of 323.3–432.1 μg/m 3 during HPE Ⅲ, although these trajectories only contributed 5.6%–11.1% of the total dominant transport pathways, while those in trajectories from the northwest were highest during HPEs Ι and Ⅱ. The highest contributions of air masses from short distances were found during HPE Ⅲ, of 77.8%, while they were only 65.6% and 47.8% during HPEs Ι and II, respectively. More attention should be given to transport pathways within the short distance from Jinan. Therefore, enhancing regional cooperation in Jinan and surrounding regions (particularly in the south, southeast, northwest, west, and north) is critical for improving air quality in the North China Plain. Graphical abstract: Image 1 Highlights: The number of HPEs decreased from 2013 to 2017, then increased from 2017 to 2019. Contribution of secondary components increased as HPEs progressed. Dominant trajectories derived from south and southeast regions. Trajectories from northwest, west, and north contained high PM2.5 concentrations. Short-distance transmission highly contributed to HPEs.